The law of damages in international sales : the CIS and other international instruments - Saidov, Djakhongir (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2021)
"The second edition of this internationally acclaimed book explores damages for breach of an international sales contract, one of the most important and frequently invoked remedies. The focus is on the international contract law instruments such as the Convention on Contracts for the International Sale of Goods (CISG), the UNIDROIT Principles of International Commercial Contracts and the Principles of European Contract Law. The book draws on the experience of some major legal systems and engages with legal scholarship on the international instruments and on contract damages, providing the most comprehensive, in-depth and thorough examination of damages under the instruments to date. The second edition is updated, reflecting the latest developments in legal thinking on contract damages. It incorporates around 60 new cases and now covers more than 370 cases decided by courts and arbitration tribunals from around the world. The new edition is substantially revised, including new commentary on damages for a documentary breach. Truly international in spirit, this book is analytically rigorous and practically oriented, offering distinctive analyses of, and solutions to, some of the most challenging problems surrounding contract damages"--
Introduction -- General part of the law of damages -- Categories of loss -- Causation -- Foreseeability 00 Mitigation -- Standards of proving loss and determining the amount of damages -- Calculation of damages (Part I) -- Calculation of damages (Part II).
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Export sales contracts; Damages; Sale of goods law; Electronic books